Determinants of Early Postpartum Psychological Reaction among Mothers in Kuala Lumpur Hospital - M, Ramli; AAW, Abdullah; MIB, Saiful; MN, Hafiz; AAZ, Fahmi (IIUM Medical Journal Malaysia, 2010)
Introduction: Maternal psychological well-being determines early mother-infant relationship and baby’s health. Paying attention on this aspect is essential particularly in early postpartum period. This study aimed to determine early psychological reactions toward socioeconomic profiles, delivery methods and delivery outcomes among postpartum mothers in Kuala Lumpur Hospital. Materials and Methods: A total of 150 twoweek-postpartum mothers participated in this cross sectional study and their psychological perspective was measured by using the Depressive, Anxiety and Stress Scale (DASS). Results: 4%, 16% and 4.7% of respondents had significant depressive, anxiety and stress levels respectively. Conclusion: Socioeconomic variables such household income, level of education and presence of medical illness were statistically significant to determine early postpartum psychological reactions but not the modes or outcomes of delivery.